2019
DOI: 10.1103/physrevb.99.054105
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic bending flexoelectric constants in two-dimensional materials

Abstract: Flexoelectricity is a form of electromechanical coupling that has recently emerged because, unlike piezoelectricity, it is theoretically possible in any dielectric material. Two-dimensional (2D) materials have also garnered significant interest because of their unusual electromechanical properties and high flexibility, but the intrinsic flexoelectric properties of these materials remain unresolved. In this work, using atomistic modeling accounting for charge-dipole interactions, we report the intrinsic flexoel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
80
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(89 citation statements)
references
References 76 publications
7
80
1
1
Order By: Relevance
“…(20) is the average of O in the maximally mixed state of H ⊗k , which does not equal the right-hand side of Eq. (17). If |E i1 , .…”
Section: B Definition Of K-ethmentioning
confidence: 99%
See 4 more Smart Citations
“…(20) is the average of O in the maximally mixed state of H ⊗k , which does not equal the right-hand side of Eq. (17). If |E i1 , .…”
Section: B Definition Of K-ethmentioning
confidence: 99%
“…, which implies that all the kth moments of ν equal those of the HRU [5][6][7]. The previous studies [12][13][14][15][16][17] revealed the fundamental relationship between unitary k-designs and information scrambling. As discussed below, on the other hand, there is a subtle issue about the relationship between unitary k-designs and Hamiltonian dynamics [12].…”
Section: A Basic Ideamentioning
confidence: 99%
See 3 more Smart Citations